Semiautomated correlative 3D electron microscopy of in vivo- imaged axons and dendrites - Maco, Bohumil; Cantoni, Marco; Holtmaat, Anthony; Kreshuk, Anna; Hamprecht, Fred; Knott, Graham W. (Nature protocols, 2014)
The authors describe an approach that can be used after in vivo imaging of dendrites and axons in adult mouse brains to prepare and image fluorescent structures of interest using focussed ion beam scanning electron microscopy.